The Right to information act, 2005 ( 22 of 2005) - Arora, Krishna (New Delhi, 2005)
The Right to Information Act 2005 is a legislation passed after years of people's struggle for securing a transparent, accountable and public participatory governance. The passing of this law by Parliament marks a notable milestone in the evolution of the Indian democracy.
Keywords: Right to information act-2005